TNBS-induced colitis in rodents: preliminary results of a chronic model - Silva, Inês (2020)
Background: Inflammatory bowel disease (IBD) is a gastrointestinal disorder characterized by chronic inflammation of the intestinal epithelium. The symptoms of IBD depend on the intestinal affected segment and usually include diarrhea often with blood, colic abdominal pain, and fecal urgency. Beyond these, other unspecific symptoms may occur like fever, loss of appetite and weight, fatigue, and primary amenorrhea. Nowadays, used therapy in IBD consists of salicylates, corticosteroids, immunosuppressants, and biological therapy. These drugs aim to induce and/or maintain the patient in remission and ameliorate the disease’s secondary effects, rather than modifying or reversing the underlying pathogenic mechanism. Aim: Development of an animal model of trinitrobenzene sulfonic acid (TNBS)-induced chronic colitis in order to evaluate the influence of new drugs in the IBD.